Fábchich József Pindarosa - Imre, Flóra (Studia Litteraria, 2024)
This study is an introduction to the work of József Fábchich. Fábchich started translating Greek poems in their original metres around the end of the 18th century. The only work he published is a volume that appeared in 1804, comprising the Odes of Pindar and a few pieces by Aeolic lyric poets. This article analyses this volume, arguing that Fábchich’s work is rather paradoxical from numerous perspectives. Firstly, he keeps the original metres and he seems to have read the secondary literature available at the time on Pindar, but in the end, his metrical practice is based on his own particular ideas. Secondly, he wishes to contribute to the development of the Hungarian language with his translations, but it seems that the texts he produced were hard to read even for his contemporaries. The study concludes that Fábchich was an thought-provoking and colourful character of this phase of the history of translation into Hungarian, but his oeuvre and his influence does not bear comparison with more successful contemporaries like Benedek Virág.